Additive manufacturing of geopolymer for sustainable built environment - Panda, Biranchi (2018)
This paper evaluates the potential of fly ash based geopolymer cement for large scale additive manufacturing (AM) of construction elements. Geopolymer is considered as a green construction material and its use in AM may contribute towards sustainable environment since in AM process material is only deposited whereby it is necessary. As part of this research, an industrial robot was employed to print geopolymer mortar in layer-by-layer manner directly from 3D computer-aided design (CAD) model. The characteristic of raw materials and fresh properties were examined by rheology, x-ray diffraction (XRD), and scanning electron microscopy (SEM). Mechanical tests such as compression, flexural and tensile bond strength were conducted on the printed geopolymer in different printing directions and their performance was compared with casted samples. It was found, from the experimental results, that the mechanical properties of 3D printed geopolymer are mostly dependent of loading directions due to anisotropic nature of the printing process and retains intrinsic performance of the material.